Experimental Studies of OSB Laminated Beams and I-beams Made of Wood and Wood-based Materials - Denisiewicz, Arkadiusz; Socha, Tomasz; Kula, Krzysztof (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The article presents the results of comparative studies of I-beams and laminated beams made of OSB boards, aimed at demonstrating the impact of flange joint defects in I-beams on their load-bearing capacity and at presenting an alternative structural solution. As part of the experimental research, destructive bending tests were carried out on beams with a span of 540 cm and a cross-sectional height of 30 cm, in accordance with EOTA guidelines. The results revealed a significant sensitivity of I-beams to the presence of material defects in the flanges. In contrast, the double-glued laminated beams, despite their slightly lower stiffness, achieved substantially higher load-bearing capacities as well as more repeatable and predictable behavior. The analysis showed that OSB laminated beams can be a viable alternative to I-beams in applications where greater reliability is required.
Keywords: laminated beams; wood; wood-based materials; I-beams; experimental studies